Toward an innovation radar for cultivated meat: exploring process technologies for cultivated meat and claims about their social impacts - Woelken, Lisa; Weckowska, Dagmara M.; Dreher, Carsten; Rauh, Cornelia (Frontiers in Sustainable Food Systems, 2024)
Cultivated meat has received growing attention since the technology has the potential to produce meat more ethically and sustainably than the current meat production. However, this technology faces major challenges, which can be divided into four main categories: cell line development, scaffolding, growth media, and bioprocess, which need to be overcome to reach industrial production levels. Technological innovations have been proposed to overcome those challenges. Nevertheless, those technologies have not been evaluated based on their social sustainability yet. This review provides an overview of the existing technologies in those four categories. An innovation radar for cultivated meat is proposed allowing to explore the directionality of the proposed innovations towards social sustainability. The technologies in the areas cell line development, scaffolding, growth media, and bioprocess are expected to have an impact on inclusion in consumption of cultivated meat. Some cell innovations are expected to raise cognitive barriers due to complex technologies that might be difficult for the consumer to understand. Cultural barriers are anticipated to be raised by cell innovation entailing genetic engineering and medium innovation using FBS or animal components, which is considered to harm animals. Further, regulatory barriers are expected in the EU if genetic modification is used in the production process, which concerns the areas cells, media, and scaffolding. The innovations for scaffolds are expected to mainly lower cost and cultural barriers since most technologies are already used in the food industry. Bioprocess innovations promise to lower cost and capability barriers, however it must be considered, that most of the collected data for innovations in the bioprocess domain are based on assumptions.